THE ROLE OF SCHOOLS IN ESPORTS DEVELOPMENT AMONG YOUNG PEOPLE - Nilan, Fariha (ASEAN Journal of Sport for Development and Peace, 2022)
eSports has created a promising digital industry development. The benefits that come and the challenges in understanding eSports must also be explored. The IOC's movement informing the Olympic Virtual Series activities must be responded to by sports practitioners or people who focus on sports as demands and adaptations in sports development. The formation of the Indonesia eSports Association (IeSPA) under the guidance of the Komite Olahraga Rekreasi Masyarakat Indonesia (KORMI) and registered as a member of the Komite Olimpiade Indonesia/National Olympic Committee (KOI/NOC) and Esport Indonesia (ESI) is officially recognized as a member of the Komite Olahraga Nasional Indonesia (KONI). This article contains a literature review that discusses eSports that must be taken seriously to organize the future by focusing on the plan to respond to eSports. eSports are a concern at this time. The debate whether eSports are included in sports is still the focus of many people. However, the author does not want to be protracted, so the author focuses more on preparing young people to respond to eSports, which is a positive thing. The implementation of eSports in schools, especially in Indonesia, is included as a school activity to provide students insight into eSports. Future career planning,g, and others will be possible and beneficial for the younger generation. The purpose of bringing eSports into schools is to understand that it is essential to learn what it takes to perform at an elite level and incorporate an understanding of sport into it